PENGARUH STATUS KEPEMILIKAN LAHAN TERHADAP PENDAPATAN PETANI DAN KONSOLIDASI LAHAN DI JAWA BARAT : STUDI KASUS DI KABUPATEN INDRAMAYU DAN PURWAKARTA - Morina Pasaribu; Istriningsih - Istriningsih (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
The Impacts of Land Ownership Status on Small Scale Farmers’ Income in Indramayu and Purwakarta Districts. The conversion of agricultural land in West Java in 2012-2015 amounted to 1.24% has caused a decrease in the number of farmer households, a decrease in the area of land under cultivation and a change of land tenure status. These changes have impacted on the farmers’ income. The government program, namely the Special Efforts of Soybean Corn Rice (Upsus Pajale) was expected to increase production yields which will impact the increased farmers’income. Most of the farmers who received aids of Upsus Pajale were groups of small scale farmers. This study aimed to analyze the impact of land ownership status, land area and production on the income of small scale farmers in Indramayu and Purwakarta Districts. The data collection method used a questionnaire with a total of 50 respondents in Indramayu and Purwakarta, West Java using purposive sampling. Data were analyzed quantitatively through income analysis, respondent distribution and linear regression. The results showed that the land ownership status (ownership, rent, and profit sharing) was proven to significantly affect the income of smallholder farmers in Indramayu and Purwakarta, West Java. Farmers with rental status have a lower income than farmers with owned status. This condition was caused by the additional obligation for rental farmers in the form of rent or profit sharing. Farmers showed a positive response to solutions to improve the welfare of small scale farmers through the government program UPSUS Pajale. However, farmer respondents considered this discourse less appropriate due to the reasons for fear of losing their land and jobs. The government needs to design policies and programs that are more directed at optimizing technology and knowledge-based production and strengthening land tenure in order to improve the welfare of farmers. Keywords: land conversion, income, land status, land consolidation  ABSTRAK Konversi lahan pertanian Jawa Barat pada tahun 2012-2015 sebesar 1,24% menyebabkan menurunnya jumlah Rumah Tangga Petani (RTP), menurunnya luasan lahan garapan RTP, serta perubahan status penguasaan lahan. Perubahan tersebut dapat berpengaruh pada tingkat pendapatan petani. Program pemerintah Upaya Khusus Padi Jagung Kedelai (Upsus Pajale) diharapkan dapat meningkatkan hasil produksi serta pendapatan RTP. Sebagian di antara petani penerima bantuan Upsus Pajale merupakan kelompok petani dengan penguasaan lahan relatif sempit. Penelitian ini bertujuan untuk mengetahui pengaruh status kepemilikan lahan, luas lahan, dan produksi terhadap pendapatan petani berlahan sempit di Kabupaten Indramayu dan Purwakarta. Metode pengumpulan data menggunakan kuesioner dengan total responden 50 orang di Kabupaten Indramayu dan Purwakarta, Jawa Barat, secara purposive sampling. Data dianalisis secara kuantitatif melalui analisis pendapatan, distribusi responden, dan regresi linier. Hasil penelitian menunjukkan bahwa status kepemilikan lahan (milik, sewa, dan bagi hasil) terbukti secara nyata mempengaruhi pendapatan petani berlahan sempit di Kabupaten Indramayu dan Purwakarta, Jawa Barat. Petani dengan status sewa memiliki tingkat pendapatan yang lebih kecil dari petani milik. Kondisi tersebut disebabkan adanya kewajiban tambahan bagi petani sewa berupa biaya sewa ataupun bagi hasil. Petani menunjukkan respon positif terhadap solusi peningkatan kesejahteraan petani skala kecil melalui program pemerintah UPSUS Pajale. Wacana konsolidasi lahan belum mendapatkan respon positif bagi petani karena ketakutan kehilangan tanah dan pekerjaan. Pemerintah perlu merancang kebijakan dan program yang lebih mengarah pada optimalisasi produksi berbasis teknologi dan pengetahuan serta dan penguatan status kepemilikan lahan guna meningkatkan kesejahteraan petani.Kata kunci: konversi lahan, pendapatan, status lahan, konsolidasi lahan